2003
DOI: 10.1002/pmic.200300509
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of the responses of Panax ginseng C. A. Meyer leaves to high light: Use of electrospray ionization quadrupole‐time of flight mass spectrometry and expressed sequence tag data

Abstract: We performed comparative proteomic analyses in order to understand the physiological responses of ginseng (Panax ginseng C. A. Meyer) to high light (HL). As a first step, we analyzed the proteins expressed in ginseng leaves. Proteins extracted from leaves were separated by two-dimensional polyacrylamide gel electrophoresis. Protein spots were identified by tandem mass spectra analysis using electrospray ionization quadrupole-time of flight mass spectrometry (ESI Q-TOF MS). We used a ginseng expressed sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…3␤-HSD has been implicated in the biosynthesis of the steroid cardenolide in foxglove (Digitalis lanata) (69) and has been detected in potato and tobacco, suggesting a role in general steroid metabolism (70). In a proteomics survey of Panax ginseng, the abundance of 3␤-HSD increased in response to light and was linked to the biosynthesis of steroidal saponins (71). 3␤-HSD was also increased in abundance in rice challenged with a fungal pathogen suggesting an involvement in the biosynthesis of defense-associated steroids (72).…”
Section: Lc-ms/ms Using Public and Opium Poppy-specific Databases-mentioning
confidence: 99%
“…3␤-HSD has been implicated in the biosynthesis of the steroid cardenolide in foxglove (Digitalis lanata) (69) and has been detected in potato and tobacco, suggesting a role in general steroid metabolism (70). In a proteomics survey of Panax ginseng, the abundance of 3␤-HSD increased in response to light and was linked to the biosynthesis of steroidal saponins (71). 3␤-HSD was also increased in abundance in rice challenged with a fungal pathogen suggesting an involvement in the biosynthesis of defense-associated steroids (72).…”
Section: Lc-ms/ms Using Public and Opium Poppy-specific Databases-mentioning
confidence: 99%
“…For proteins that were not identified by MS BLAST, peptide MS/MS data were searched against publicly available EST database. Nam et al (41) reported that EST database searches combined with MS/MS analysis could be used to identify proteins from organisms for which the full genome database is not yet available. We performed the conventional BLAST searching with the query of matched sequences found in the EST database.…”
Section: Identification Of Virulence Proteins Based On Proteomicsmentioning
confidence: 99%
“…The sample was digested with trypsin. Peptide tandem mass spectrometry analysis of the digested peptides was performed using an electrospray ionization quadrupole time-of-flight mass spectrometer as described previously (39).…”
Section: Methodsmentioning
confidence: 99%